2021
DOI: 10.37022/wjcmpr.v3i4.179
|View full text |Cite
|
Sign up to set email alerts
|

G6Pd deficiency with severe hemolytic anemia: a case report

Abstract: A 3-year-old boy presented to our atoll hospital in H.A Alif Dhidhoo, with severe pallor, jaundice, easy fatigability and recurrent episodes of passage of dark-colored urine for past 3 days. He was born mature at 39 weeks of gestation with no past significant medical history. Recent history revealed the consumption of 2 cans of fava beans and application of some medicinal herbs. On admission, physical examination revealed fever of 101 degree Fahrenheit, severe pallor, jaundice, cervical lymphadenopathy and mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has been long known and proofed by scientific studies that G6PD deficiency is geographically distributed in concordance with the spatial distribution of malaria and frequently presents when plasmodia infection is common [1][2][3]15]. According to this research the G6PD deficiency prevalence obtained was valued 21% as measured by a qualitative rapid diagnostic test.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It has been long known and proofed by scientific studies that G6PD deficiency is geographically distributed in concordance with the spatial distribution of malaria and frequently presents when plasmodia infection is common [1][2][3]15]. According to this research the G6PD deficiency prevalence obtained was valued 21% as measured by a qualitative rapid diagnostic test.…”
Section: Discussionmentioning
confidence: 69%
“…As previous studies have revealed that deficiency of G6PD does not always result in severe anemia and is typically asymptomatic until the individual is exposed to substances such as quinones (primaquine, chloroquine) [1,7,15]. The state of immunity and personal stamina plays an important role and seems to be a vital determinant for individuals with G6PD deficiency conditions to develop anemia from mild to severe.…”
Section: Discussionmentioning
confidence: 99%